“Ngababali” Tradition on Islamic Religious Practice in The Negeri Besar Village, Way Kanan, Lampung Province - Fitri Yanti; Eni Amaliah; Abdul Rahman (Institut Agama Islam Negeri Madura, 2018)
This study discusses the tradition of Ngababali at the Negeri Besar Village in Way Kanan, which is a local wisdom that until now is still practiced by the local village community, even many outside visitors who take part in the ngababali tradition. The tradition of praying for something to the grave or sacred tomb with offerings and so on. The people believe what is intended and asked for beings who are not visible or given to those who have abundant assets to be given is always easy to get sustenance or ask to be kept away from distress or when getting a disaster. The purpose of this study is to describe the religious practices that are carried out in a tradition that is still thick in that society. Qualitative analysis methods are descriptive and to facilitate data retrieval using accidental sampling. The results of the analysis show that the community productively finally places the religion and tradition of ngababali together namely religion into a belief and tradition of ngababali into a practice and belief which is then placed in the social environment forming a belief and togetherness and directing a unity to keep religion as the the main. This proves that the traditional ngababali process continued to use the Islamization process eventhough the local culture served as a bridge to the trust of the local community so that it became a productive social form.